Keats's Noises Off. Issue 2 (July 2022) - Perry, Seamus
Abstract : Robert Gittings once suggestively identified a possible connection between Keats's circumstances, living in Wentworth Place in the Spring of 1819, and a detail from the 'Ode to Psyche'. Drawing especially on the Keatsian writings of Michael O'Neill, this essay seeks speculatively to relate the representation of experience in the great odes more generally to the idiosyncratic nature of life in the double-house, shared at first with the Dilkes and then with the Brawne family. It also explores the particular significance of Shakespeare's Troilus and Cressida within this culminating moment of Keats's career, and the role of the play in his thinking about the 'poetical character' as exemplified in the odes.